The role of customer satisfaction on service quality and customer loyalty - Artanti, Yessy; Masfiyah, Irfi (Proceeding of International Management Conference and Progressive Papers, 2023)
The business world is increasingly showing its rapid development and progress in various fields. In the telecommunications, information and media sectors in particular, every company wants to be able to compete with the type of business it has, the implementation of service quality carried out by a company engaged in services is to provide the best quality of service (service) for customers. In reality, not all companies have a high level of customer loyalty including Indihome PT Telkom Access Kediri. This study aims to determine the effect of service quality on customer loyalty through customer satisfaction Indihome PT Telkom Access Kediri. The method used is multiple linear regression. With a total of 34 respondents who are customers of PT Telkom Access Kediri Based on the results of this study that service quality and customer satisfaction have a positive influence. This means that the better the quality of service and customer satisfaction provided, the better customer loyalty will be created. This indicates that the role of service quality affects customer loyalty through customer satisfaction.